ESTIVATION IN SOUTH-AMERICAN AMPHIBIANS AND REPTILES - Abe, Augusto Shinya [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 1995)
A number of amphibians and reptiles have cyclic behavior, becoming inactive with the coming of the dry season. In South America this pattern of activity is common, particularly in savannah-like vegetation. During the dry season amphibians burrow into the mud or soil, and either form a cocoon or increase the osmotic concentration of body fluids to reduce evaporative water loss. Some phyllomedusid tree frogs coat their body surface with skin secretion and excrete uric acid to minimize water loss. Reptiles also retreat into shelter deep enough to avoid temperature fluctuation during estivation or reduce metabolic response to temperature. Reduction of temperature sensitivity of the metabolism seems to be a strategy common to estivating amphibians and reptiles. Despite seasonal change of the environment, some species of reptiles are active all year round.
Keywords: SEASONALITY; DROUGHT; METABOLISM; OSMOREGULATION